Application tooling for Electrical Discharge Machine (EDM) / Mohd Nasir Ismail, Lindy Enggong and Albert Frederick - Ismail, Mohd Nasir; Enggong, Lindy; Frederick, Albert (1999)
With the advancement of teclinologv nowadays, many industrial sector exist in our country in various fields. 0 One of the fields which has high reputation and prospect is the manufacturing industry. It requires machines and computer system in producing products. Normally, Computer Numerical Control (CNC), Electrical Discharge Machine (EDM) and etc are being used. Here, we are goiug to discuss in more details concerning the EDM and its tooling. With the widesperad use of EDM, the quality and quantity of a product definitely can be obtained and increased. This is due to the high precision/accurary of EDM compared to other machines/devices. Apart from that, EDM also can be used to produce various shape of desired product which is impossisible done by the other machines. Tooling is important in determining the end product. The use of tooling in machining work gives a lot of advantages for man. Apart from producing high quality product, the use of tooling also make much easier task for the operator in dealing with the machine. In a nutshell, it is hoped that we will fully utilised all the information from this survey as a knowledge to be applied in the industrial sector.